Violência escolar, desinformação e as fakenews sobre corpos, gêneros e sexualidades nas mídias e redes sociais - Cunha Júnior, Ezequias Cardozo da (2023)
In the contemporary post-truth, the phenomenon of fakenews via media and social networks has misinformed the population through false stories that ratify moral panics derived from fears produced by cisheteronormativity. These panics echoed from the digital media and reflected in the school as actions that sought to punish, discipline and control education to ensure the reproduction of gender and sexuality norms in society, even manipulating efforts to overcome school violence. Faced with this problem, this study developed within the scope of the research line of Education in Science and Mathematics of the Graduate Program in Education (PPGED/UFU) to question what relationships emerge between the dissemination of fakenews and the of homotransphobic violence in schools? With this questioning, the research sought to investigate how the phenomenon of fakenews (re)produced resonances and echoes that ratify the cisheteronormativity and homotransphobia violence in schools. A qualitative and exploratory-descriptive approach was adopted through bibliographical and documentary research. To achieve the objective, the investigation involved the collection and classification of fakenews that conveyed discourses involving bodies, genders, sexualities and education in the media and social networks. Then, the analysis of the contents allowed demonstrating the resonances that guide gender and sexual norms in schools, reinforcing violence. In addition, the analysis of the content of news published by digital newspapers between 2021 and 2022 allowed tracking the echoes of moral panics from fakenews in control actions transmitted over teaching work and the school universe. Three moral panics mobilized by fakenews were labeled disinformation about the gay kit, gender ideology and the unisex bathroom in schools. As a result of the research, it can be stated that fakenews produce sensations of moral panic that misinform society and echo in schools as control actions over teaching work, the student body and school management. The control actions take the form of dismissal, subpoena, persecution and threat to the practice of teachers and to suspension against the student group. The control actions and fakenews have in common the fear evoked: the threat to the child. This threat is produced by political discourses, however, displaced by the false stories of fakenews into schools and the school universe, reinforcing the homotransphobia violence through the coercion of teaching training and practice. Faced with cisheteronormative misinformation (re)produced by fake news via media and social networks, the science and biology education can move beyond limited traditional approaches to the study of human anatomy and physiology to also deconstruct fears and moral panics associated with the gender and sexuality in the society.